Pioglitazone for NAFLD Patients With Prediabetes or Type 2 Diabetes Mellitus: A Meta-Analysis - Lian, Jingxuan; Fu, Jianfang (Frontiers in Endocrinology, 2021)
[Abstract] Objective: To systematically evaluate the effects of pioglitazone in the treatment of patients with prediabetes or T2DM combined with NAFLD. Methods: The Cochrane Central Register of Controlled Trials (CENTRAL), Embase, and ClinicalTrials databases were searched until August 2020 for publications written in English. Two reviewers independently assessed study eligibility, continuous data extraction, independent assessment of bias risk, and graded the strength of evidence. Our primary outcomes were the individual number of patients with improvement of at least 1 point in each of the histological parameters. Baseline characteristic data, such as BMI, weight, total body fat, fasting plasma glucose and fasting plasma insulin, and liver biological indicators, such as triglyceride level, HDL cholesterol level, plasma AST, and plasma ALT, were used as secondary outcomes. Results: A total of 4 studies were included. Compared with placebo, pioglitazone significantly improved steatosis grade, inflammation grade and ballooning grade, while in the fibrosis stage, there was no significant improvement in pioglitazone compared with placebo. In addition, pioglitazone can also improve blood glucose and liver function. Conclusion Pioglitazone can significantly improve the histological performance of the liver and insulin sensitivity. Additionally, it can significantly reduce fasting blood glucose, glycosylated hemoglobin, plasma AST, ALT and other liver biological indicators. Due to the lack of relevant randomized controlled trials and short intervention times, long-term studies are still needed to verify its efficacy and safety.